1988
DOI: 10.1126/science.3420404
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biogenic Hydrocarbons in Urban Photochemical Smog: Atlanta as a Case Study

Abstract: The effects of natural hydrocarbons must be considered in order to develop a reliable plan for reducing ozone in the urban atmosphere. Trees can emit significant quantities of hydrocarbons to metropolitan areas such as Atlanta, and model calculations indicate that these natural emissions can significantly affect urban ozone levels. By neglecting these compounds, previous investigators may have overestimated the effectiveness of an ozone abatement strategy based on reducing anthropogenic hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
601
2
19

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(634 citation statements)
references
References 11 publications
12
601
2
19
Order By: Relevance
“…The loss rate of ozone increases with the addition of the isoprene source because of the direct reaction of ozone with the double carbon-carbon bonds in isoprene. This is in contrast to the situation over most of the contiguous United States, where isoprene emissions contribute to ozone formation (Chameides et al, 1988). The reason is the relatively low NO x (NO x = NO + NO 2 ) concentrations used in the model (see Table 2 for initialization values for all chemical species).…”
Section: Atmospheric Chemistry Modellingcontrasting
confidence: 39%
See 1 more Smart Citation
“…The loss rate of ozone increases with the addition of the isoprene source because of the direct reaction of ozone with the double carbon-carbon bonds in isoprene. This is in contrast to the situation over most of the contiguous United States, where isoprene emissions contribute to ozone formation (Chameides et al, 1988). The reason is the relatively low NO x (NO x = NO + NO 2 ) concentrations used in the model (see Table 2 for initialization values for all chemical species).…”
Section: Atmospheric Chemistry Modellingcontrasting
confidence: 39%
“…Once isoprene enters the atmosphere, it has profound effects on regional air quality (Chameides et al, 1988), the global oxidizing capacity of the atmosphere (Crutzen and Zimmermann, 1991), and secondary organic aerosol production (Andreae and Crutzen, 1997). Isoprene emissions are modelled using algorithms derived from the leaf-level response of emissions to variations in temperature and light, which have mechanistic underpinnings (Guenther et al, 1993;Grote and Niinemets, 2008;Monson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tropospheric oxidation, in turn, determines the lifetime of numerous atmospheric constituents, including methane and carbon monoxide. Biogenic isoprene emission also contributes to the generation of tropospheric ozone in urban atmospheres (Chameides et al 1988). Given its prominent role in tropospheric oxidative chemistry, it is important to understand the ecological and physiological controls over isoprene emission as part of the emerging integration of biosphere/atmosphere processes.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies within this range should be conducted with a high priority since many of the high ozone episodes reported for the southeastern United States occur during the hottest parts of the summer. Isoprene emission from urban forests in this region is known to play an important role in these events (Chameides et al 1988).…”
mentioning
confidence: 99%
“…The net result is that, in heavily vegetated regions, the emissions from biogenic and anthropogenic sources are equally important. Chameides et al (1988) showed that in Atlanta, biogenic emissions alone were sufficiently high to cause predicted levels of ozone above the National Ambient Air Quality Standards limit of 12pphin ozone.…”
Section: Emissionsmentioning
confidence: 99%